Additively-Manufactured, Magnetically Controlled, Frequency and Polarization Reconfigurable Phased Array Antenna - Ulan Myrzakhan; Farhan A. Ghaffar; Mohammad Vaseem; Atif Shamim (IEEE Open Journal of Antennas and Propagation)
An additively manufactured phased array antenna is presented in this work that provides simultaneous reconfiguration in frequency, polarization, and beam direction solely in response to magnetic tuning of the underlying ferrite substrate. This design obviates the need for integrated active components, which have been fundamental elements enabling tuning operation in traditional reconfigurable array antennas. The array element of the proposed array antenna consists of a waveguide-based phase shifter, realized by printing metallic walls on a ferrite substrate, which is then monolithically integrated with a printed circular patch antenna. Depending on the magnitude and polarity of the applied magnetic field (solenoids) to the patches, the array antenna can operate in a linearly polarized (LP) mode at 7.2 GHz or in dual circularly polarized (CP) modes in two continuously tunable frequency bands, 5.9–6.5 GHz and 7.6–7.95 GHz. Simultaneously, when magnetic field is applied to the phase shifters, continuous beam steering within ±25° of the boresight can be realized (±35° when fully saturating the ferrite at the phase shifters). To the best of the authors’ knowledge, this is the first implementation of an additively manufactured and fully magnetically controlled array antenna of this versatility.